The Role of Student Self-Government in Ensuring the Quality of Higher Education - Oksana Kondur; Nataliia Koturbash; Galyna Mykhaylyshyn (Journal of Vasyl Stefanyk Precarpathian National University)
The current state of development of the Ukrainian state requires further reform of all spheres of life of the Ukrainian community. The democratization of the principles of higher education needs special attention. Since students are the driving force of society, the developer of unique ideas of the present and future, a factor in the formation and development of civil society, so the democratization of student life, active participation of students in different organizations, leadership skills and teamwork, making the right decisions and responsibility for their implementation becomes especially relevant during educational transformations.